A review of the photocatalytic degradation of organic pollutants in water by modified TiO2 - Li, Xueqi (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Organic pollutants in water bodies pose a serious environmental problem, and photocatalytic technology is an efficient and environmentally friendly water treatment method. Titanium dioxide (TiO2) is a widely used photocatalyst, but it suffers from some drawbacks such as a narrow light response range, fast charge recombination, and low photocatalytic activity. To improve the photocatalytic performance of TiO2, this article reviews the preparation methods, performance evaluation, and applications of modified TiO2 photocatalysts. Firstly, the article introduces the effects of doping modification, semiconductor composite modification, and other modification methods on the structure and properties of TiO2 photocatalysts, as well as the common characterization techniques and activity test methods of photocatalysts. Secondly, the article discusses the effects and mechanisms of modified TiO2 photocatalysts on degrading dye, pesticide, and other organic pollutants in water bodies, as well as the influencing factors. Finally, the article summarizes the main achievements and advantages of modified TiO2 photocatalysts in degrading organic pollutants in water bodies, points out the existing problems and challenges, and prospects for the development direction and future of this field